Influence of the inclusion of soaked and peeled jack bean meals in the broiler ration on internal vital organs, digestive tract organs, and intestinal villi morphology - Sakinah, Raudhoh Gholia; Alifianty, Ouldya Fasya; Hermana, Widya; Nahrowi, Nahrowi; Ridla, Muhammad (State Islamic University of Sultan Syarif Kasim Riau, 2024)
ABSTRACT. Jack bean (Canavalia ensiformis L.) is a potential alternative protein source to replace soybean meal in local feed formulations. While jack beans are high in protein, their high levels of anti-nutritional factors limit their use. Identifying effective processing techniques to improve the quality of jack beans is therefore essential. This study examines the effects of incorporating soaked and peeled jack bean meal into broiler diets on internal organs, digestive organs, and intestinal villi morphology. The jack beans were processed by soaking for 3 hours, peeling, oven drying, and grinding into meal form. A completely randomized design was used, with three levels of processed jack bean inclusion (0% JBM0, 5% JBM5, and 10% JBM10), each replicated six times. Data were analyzed using analysis of variance (ANOVA), followed by a post hoc Tukey test for significant findings. The results indicated that soaking for 3 hours and peeling effectively lowered the hydrogen cyanide (HCN) content from 207.61 ppm to 51.21 ppm. The inclusion of processed jack bean meal had no significant impact (P>0.05) on internal organs, digestive tract organs, or intestinal villi morphology. These findings suggest that processed jackbean meal can replace soybean meal in poultry feed at levels up to 10% without adverse effects on internal organs.